1989
DOI: 10.1083/jcb.109.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock resistance conferred by expression of the human HSP27 gene in rodent cells.

Abstract: Abstract. Heat shock induces in cells the synthesis of specific proteins called heat shock proteins (HSPs) and a transient state of thermotolerance. The putative role of one of the HSPs, HSP27, as a protective molecule during thermal stress has been directly assessed by measuring the resistance to hyperthermia of Chinese hamster and mouse cells transfected with the human HSP27 gene contained in plasmid pHS2711. One-and two-dimensional gel electrophoresis of [3H]leucineand [32P]orthophosphate-labeled proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
349
1
9

Year Published

1996
1996
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 653 publications
(374 citation statements)
references
References 41 publications
15
349
1
9
Order By: Relevance
“…Expression of Hsp27 had no detectable e ect on the levels of other heat-shock protein, Hsp70 (Landry et al, 1989). Cyt c-dependent activation of cas-3 was then analysed after addition of cyt c/dATP.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of Hsp27 had no detectable e ect on the levels of other heat-shock protein, Hsp70 (Landry et al, 1989). Cyt c-dependent activation of cas-3 was then analysed after addition of cyt c/dATP.…”
Section: Resultsmentioning
confidence: 99%
“…10 Several studies have shown that overexpression of HSP27 is linked to resistance to heat shock and to a variety of chemotherapeutic drugs in different cell types [11][12][13] but not to radiation. 14 HSP27 was found to be downregulated in the radiosensitive cell line, which suggests a possible role of HSP27 in determining radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…sis in in vitro cultured cells. [28][29][30][31][32][33][34]62 Thus, the opposite behavior of AI and Hsp27 levels, in normal liver and N12, with the highest AI in correspondence with the lowest Hsp27 level, and peak Hsp27 values in correspondence with low AI, suggests that Hsp27 may contribute, together with recovery of the expression of antiapoptotic genes of Bcl-2 family, to the decrease in apoptosis in these tissues after the peak value at 4 hours. A different situation seems to exist in atypical liver lesions, which exhibit persistent apoptosis even in the presence of relatively high Hsp27 levels (i.e., at 18 hours).…”
Section: Table 3 Effect Of Amph Treatment On Expression Of Apoptosismentioning
confidence: 99%